Crassula argentea Jade Plant: FPS153/FP153, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the jade plant (Crassula argentea), detailing its characteristics, growth conditions, and uses. It highlights the plant’s adaptability to various light conditions and its high drought tolerance, making it suitable for both indoor and outdoor settings. The document also discusses the plant’s slow growth rate, potential height and spread, and its minimal pest and disease issues. Additionally, it notes the jade plant’s infrequent blooming, propagation methods, and the importance of well-draining soil to prevent root-rot. Original publication date October 1999.